Investigative skills to write and disseminate findings in students of a private university in Ica - Romanì Pillpe, Guillermo (2023)
The objective of this study was to determine how the investigative skills to write and disseminate findings in university students from a university in Ica. For this, the study uses the quantitative paradigm; experimental design, and pre-experimental level. The population consisted of 69 students enrolled in the general course —Written Communication Workshop—; and the specialties Systems Engineering, Nursing and Psychology. The results obtained through the non-parametric Wilcoxon T test; indicated that there were statistically significant differences between the posttest in relation to the pretest. A value of p<0.01 was obtained and we accepted H1. The results show that the revelation of the development of investigative skills works when writing and disseminating findings in university students.